ANALISA STRATEGI PRODUKSI UMKM CUANGKI LIDAH DI DESA MANGKURAYAT - Andriyas Kurniawan, Wahyu; Zihan Fitria Azzahra; Vira Syahrani Rahayu; Rizky Nurochman; Irwanto; Raihan Ikhlasul Amal; Fajar Puniman; Gilang Arbiansyah; Romi Yusnandar; Virzza Rahmaliyadi; Dellina Bella Azahra; Muhammad Rafi Yudhaputra; Meilan Widianti Sari; Agung Nugraha; Agung Gumelar; Ivan Prayoga; Kikan Abdi Negara; Ikhwan Dzaky Bima Alwi; Muchlas Taufik; Jejen Suryana (Institut Teknologi Garut, 2025)
This study aims to determine the right strategy that must be carried out by Cuanki Lidah in Mangkurayat Village, so that it can increase its competitiveness. The method used is the Strength Weakness Opportunity Threat (SWOT) analysis method. Respondents in this study were producers and sellers in the market. The sampling technique used was incidental sampling with a total of 20 respondents. The results of the study based on IFAS were 3.24 and EFAS were 0.45. This shows that the company's position is in quadrant 1 (aggressive strategy), so the strategy that must be carried out is to increase production capacity and utilize digital access in marketing, so that this Cuanki Lidah UMKM can increase its competitiveness.